The prices in the crises: What we are learning from 20 years of health insurance in low- and middle-income countries - Das, Jishnu and Do, Quy-Toan (Journal of Economic Perspectives)
Governments in many low- and middle-income countries are developing health insurance products as a complement to tax-funded, subsidized provision of healthcare through publicly-operated facilities. We discuss two rationales for this transition. First, health insurance would boost fiscal revenues for healthcare, as post-treatment out-of-pocket payments to providers would be replaced by pre-treatment insurance premia to health ministries. Second, increased patient choice and carefully designed physician reimbursements would increase quality in the healthcare sector. Our essay shows that, at best, these objectives have only been partially met. Despite evidence that health insurance has provided financial protection, consumers are not willing to pay for unsubsidized premia. Health outcomes have not improved despite an increase in utilization. We argue that this is not because there was no room to improve the quality of care but because behavioral responses among healthcare providers have systematically undermined the objectives of these insurance schemes.- Reproduced